Drawing identity: Beginning pre-service teachers’ professional identities - Beltman, Susan; Glass, C.; Dinham, Judith; Chalk, Beryl; Nguyen, Bich (Western Australian Institute for Educational Research Inc., 2015)
© 2015, Western Australian Institute for Educational Research Inc. All rights reserved. Developing a professional teacher identity can be complex as pre-service teachers engage with a process informed by their previous experiences of teachers and teaching, by learning in their pre-service course, by field placements, and by societal expectations. Using drawing as the method for gathering data, pre-service teachers in an Australian university were asked, prior to their first professional experience, to draw themselves as the teacher they hoped to become. Drawings (N=125) were coded according to the presence or absence of teacher, students and artefacts of teaching. Representations indicated that pre-service teachers identified themselves as teachers who would conduct enjoyable learning experiences, have positive relationships with their students and who were confident in themselves as a teacher. There was little evidence of the potential complexities or challenges of teaching, raising a dilemma for teacher educators in how to prepare pre-service teachers for the reality of the workplace while maintaining their positive approach.